Mechanical properties of half-Heusler alloys. (1st April 2016) - Rogl, G.; Grytsiv, A.; Gürth, M.; Tavassoli, A.; Ebner, C.; Wünschek, A.; Puchegger, S.; Soprunyuk, V.; Schranz, W.; Bauer, E.; Müller, H.; Zehetbauer, M.; et al.
Abstract: As half-Heusler compounds are promising candidates for environmentally friendly and low-cost thermoelectric materials, not only a high figure of merit and efficiency are necessary but also detailed knowledge of mechanical properties and thermal expansion is compulsory. Although these properties are quite important to evaluate mechanical stability of a thermoelectric device under mechanical stress in a temperature gradient, they have been scarcely reported in the literature. The present article comprises a series of new data of hardness and elastic moduli (in some cases in dependence on composition, density and/or temperature), fracture resistance and thermal expansion, measured with various methods and equipments, as well as a comprehensive compilation of mechanical properties of p- and n-type half-Heusler alloys hitherto available in the literature. Wherever available, experimental data are compared with those from DFT model simulations. Graphical abstract: